Sensory characteristics of instant noodles manufactured with rice-mungbean and cassava starch - Felizardo, Ma. Karina C.; Galvez, Flor Crisanta F. (1997.)
Rice-mungbean flour (70:30 mixture) was utilized as substitute for wheat flour in the production of instant noodles at levels of 0%, 10%, 20%, 30%, 40% and 50%. Potato starch was completely substituted with cassava starch. Sensory evaluation was conducted with 24 consumer panelists using 150-mm unstructured line scales to evaluate the important sensory attributes of the noodles. Consumer purchase intents were likewise determined. Results showed significant differences between the samples substituted with rice-mungbean flour only in color and surface texture when potato starch was used. The samples that were further modified with the use of cassava starch were found to be significantly different from each other in terms of all sensory attributes except hardness. More than 50% of the panelists were willing to buy the samples at a price less than P3.50/60 g pack.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Noodles; Cassava starch; Mung bean